Since 2017, the countries of the Central American Integration System experienced +250 transformations in their political, institutional and financial frameworks toward scaling Climate Smart Agriculture. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Following the launch of the CSA strategy for the Central American Integration System (2017), supported by CCAFS, actors from all levels (local, national, regional/international) implemented 259 transformations aligned with the strategy’s objectives toward scaling Climate Smart Agriculture. These transformations include CSA policy formulation and implementation, capacity strengthening and partnership around CSA, mechanisms to facilitate and articulate climate financing. Most of the transformations are concentrated in the policy area. Guatemala and Costa Rica experienced more change in the region.